Consumer Intention to Buy Organic Personal Care Products - Mayank Chhajed, Dr. Chetan Panse (International Journal of Advanced Science and Technology, 2020)
In the recent years we have observed that the significant change is there in the consumer behavior in the cosmetics segment. Consumers interest and preference have increased when it comes to products with natural ingredients, sustainable packaging, and other green elements. Consumers have started choosing the products based on features like health, natural, organic instead of size, color, flavor etc. This shift in behavior has been seen in both the consumers and producers. With the increase in awareness and knowledge as well as the disposable income, the consumer has become more quality centric. As a result, a trend is seen in the natural cosmetics segment. The research explores what are the major factors that drive a consumer to buy a natural cosmetic. This research is aimed at determining the factors that drives the intention of the consumer to buy a natural cosmetic. It focuses on determining which of the factors is the most important and considered in mind of a consumer at the point of purchase. The factors that determine the intention includes economic value, social value, hedonic value, altruistic value, price, effectiveness, trend among others. The study is done on the basis of secondary as well as primary data. It has accounted around 120 responses in total. The research attempts an empirical study to understand and apply the most likely intentions to buy natural personal-care products. The exploratory factor analysis was conducted on the gathered data using SPSS software. The conclusions were then drawn after the findings processed.